2016
DOI: 10.3892/or.2016.4788
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a inhibits cell migration and invasion by targeting RhoA in breast cancer

Abstract: MicroRNAs (miRNAs) function as genetic modulators that regulate gene expression and are involved in a wide range of biological roles, including tumor cell migration and invasion. In the present study, we demonstrated that the migration and invasion activity in MDA-MB-231 breast cancer cells could be directly influenced by altering miR-146a expression. The expression of RhoA and miR-146a in the breast cancer cells showed an inverse correlation. Upregulation of miR-146a in the MDA-MB-231 breast cancer cells by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…Accumulating evidence suggested that miR-146a acted as a tumor suppressor or an oncogene in multiple cancers. For example, miR-146a had a low expression in HCC tissues ( 24 ), breast cancer ( 25 ). On the contrary, miR-146a was found to be elevated in colorectal cancer ( 26 ), oral carcinoma ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that miR-146a acted as a tumor suppressor or an oncogene in multiple cancers. For example, miR-146a had a low expression in HCC tissues ( 24 ), breast cancer ( 25 ). On the contrary, miR-146a was found to be elevated in colorectal cancer ( 26 ), oral carcinoma ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR‐146a suppressed breast cancer metastasis to the lung in a mouse model (Hurst et al, ). Another group also found miR‐146a to act as a tumor suppressor by validating its targeting of RhoA in MDA‐MB‐231 cells, inhibiting migration (Liu, Wang, et al, ). IRAK1 and TRAF6 were further validated as targets, and miR‐146a was also implicated in enhancing apoptosis (Liu, Liu, et al, ).…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 97%
“…Alternatively, a miRNA binding of a target transcript can result in translational up-regulation [ 34 ] within their mRNA resulting in inhibition of translation or mRNA degradation [ 35 ]. Overall, miRNAs are recognized as potent regulators of eukaryotic gene expression at the post-transcriptional level [ 36 , 37 ] that regulate cell differentiation [ 38 ], migration [ 39 ], and neuronal development [ 40 ]. Approximately 256 D .…”
Section: Introductionmentioning
confidence: 99%